Comparison of different tungsten precursors for preparation of tungsten nanopowder by RF induction thermal plasma. (January 2020) - Shin, Dongyoon; Swain, Basudev; Han, Chulwoong; Kim, Yonghwan; Lee, Chan-Gi; Park, Kyung-Soo
Abstract: Tungsten nanopowders were synthesized using three different precursors: commercial tungsten (W), tungsten trioxide (WO3 ), and ammonium paratungstate (APT) by radio-frequency (RF) induction thermal plasma in the presence and absence of H2 . The crystalline structure, morphology, and particle size of the synthesized tungsten nanopowders were analyzed by X-ray diffraction, field emission scanning electron microscopy, and transmission electron microscopy. The W nanopowder obtained using APT precursor was found to be the most homogeneous and smallest nanoparticles and showed the largest α-W phase (stable) fraction, which is the preferred phase for tungsten because of its superior properties to those of the β-W phase (metastable). Highlights: Tungsten nanopowder was synthesized by RF induction thermal plasma. Three different commercial W, WO3, and APT precursors were compared. In all cases of the precursors, in the presence of H2, W nanopowder was synthesized. Precursor APT could provide W nanopowder of better quality than W and WO3 .